If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(3/4)*(4-x) = 3*x-3 // - 3*x-3
(3/4)*(4-x)-(3*x)+3 = 0
(3/4)*(4-x)-3*x+3 = 0
3/4*(4-x)-3*x+3 = 0
3/4*(4-x)-3*x+3 = 0
3-15/4*x+3 = 0
6-15/4*x = 0
6-15/4*x = 0
6-15/4*x = 0 // - 6
-15/4*x = -6 // : -15/4
x = -6/(-15/4)
x = 8/5
x = 8/5
| 10-8/9x=-9 | | 3/10+[-1/5]= | | 2t^2-7t+5=0 | | 3/4(x-4)=-3+3x | | 10y-15=25 | | 3/4(x+4)=-3+3x | | 2*18(x+3)=34 | | 3x-6x+5-7x+8= | | Cw+w-cm-m=0 | | r-43=-33 | | v^2-15v+54=0 | | -2p+5p-9=3(p-4)-5 | | (3z+1)(4z+1)(6z+1)(12z+1)=2 | | 7x-4=3x+1+9x-5 | | -4-7x=2x+15 | | 4r-9=55 | | 4x+14(-14)-3+(-14)= | | 16+8x=24+6x | | -4(-x+4)=-4x+16 | | 16-4x= | | 7x-4=-3x+1+9x-5 | | x(30-x)=176 | | -94=-17+-7m | | -4(x-4)=-4x+16 | | 7n=50+35 | | 5x-10=14+7x | | 0.2x+0.15(50)=25.5 | | 5=RAIZ(2)+6RAIZ(3)+RAIZ(2)-2RAIZ(3) | | (-9r^3+2r-1)-(-5r^2+6x^2)= | | y=x(x^2-3) | | 8w-21=11 | | -3(-4-6y)+7(-y-5y)=-8 |